Pengaruh Beban Kerja dan Burn Out terhadap Stres Kerja pada Karyawan Kilang Polypropylene Pertamina Refinery Unit (RU) III Plaju - Meilika, Rizqia; Muhammad Ichsan Hadjri; Zunaidah (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The aim of the study is to determine the effect of workload and burn out on employee work stress of Polypropylene Refinery Pertamina RU III Plaju. The population in this study were all employees at Polypropylene Refinery Pertamina RU III Plaju which consists 54 employees. This study uses a saturated sampling technique. The data used in this study is primary data with data collection techniques through questionnaires. The data analysis technique used is multiple linear regression analysis. Based on the research shows that Workload has a positive and significant effect on Employee Work Stress, Burn Out has a positive and significant effect on Employee Work Stress and Workload and Burn Out has a positive and significant effect on Employees Work Stress at Polypropylene Refinery Pertamina RU III Plaju.